The acute effects of exercising in air pollution: a systematic review of randomized controlled trials - Hung, A., Nelson, H.; Koehle, M. S. (Sports Medicine, 2022)
Background: The acute effects of air pollution (AP) exposure during physical activity have been studied. However, comprehensive systematic reviews are lacking, particularly regarding moderate-to-vigorous physical activity (MVPA). Objective: Our objective was to determine the acute health- and exercise-related effects of AP exposure during a bout of MVPA in healthy individuals. Methods: We searched for randomized controlled trials in MEDLINE, Embase, Cochrane CENTRAL, SPORTDiscus, Agricultural and Environmental Science Database, ClinicalTrials.gov, International Standard Randomised Controlled Trial Number Registry, and the World Health Organization (WHO) International Clinical Trials Registry Platform up to July 2020 without language or date restrictions. Studies including healthy subjects engaging in a bout of MVPA while exposed to one or more of the following air pollutants were eligible: particulate matter, black carbon, carbon monoxide, nitrogen dioxide, ozone, diesel exhaust, and traffic-related air pollution (TRAP). Main outcome measures were markers of pulmonary function, symptoms, cardiovascular function, cognitive function, systemic inflammation, and exercise response. The evidence was synthesized by vote counting based on direction of effect. Results: In total, 53 studies were included in the systematic review. Studies employed a heterogeneous mix of exercise protocols, AP interventions, and measured outcomes. Pooled results suggest ozone exposure during MVPA has an adverse effect on pulmonary function (100% [95% confidence interval (CI) 88-100], p < 0.001; high-certainty evidence) and reported symptoms (88% [95% CI 69-96], p < 0.001; low-certainty evidence). The effect of exposure to carbon monoxide, nitrogen dioxide, small engine exhaust, or diesel exhaust during MVPA on health- and exercise-related outcomes is uncertain because of insufficient evidence and the low to very low certainty of available evidence. Discussion: The evidence is strongest for ozone, exposure to which generally induced a reduction in pulmonary function and increased symptoms during MVPA. The research related to other outcome domains remains inconclusive. Although long-term exposure to AP is proven to be hazardous, the evidence for healthy individuals to forgo MVPA during periods of high (non-ozone) pollution remains weak.